til RvT 77: Afkolonisering af religionsvidenskaben? Et essay om Jørn Borups Decolonising the Study of Religion. Who Owns Buddhism? og relaterede diskussioner i IAHR - Jensen, Tim (Religionsvidenskabeligt Tidsskrift, 2026)
ENGLISH ABSTRACT: The essay first presents and discusses Decolonising the Study of Religion. Who Owns Buddhism? (2023) by Jørn Borup, including Borup’s characterization of decolonization as a social and ideological, but also academic and scholarly, activist project driven by indignation and identity. A project that views the academic study of religion/s—e.g. as promoted by the International Association for the History of Religions (IAHR)—as rooted in and still permeated by colonial, secular, Euro- and Christocentric modes of thought; a project that will not stop at critique but seeks to radically transform academic and disciplinary norms within the study of religion/s. Taking as its point of departure a question asked by Borup - namely whether the IAHR in the future will or can avoid being influenced and transformed by more radical decolonial approaches—the author situates Borup’s account and critical evaluation of the decolonization project within a historiographical and disciplinary context related to the IAHR’s global expansion and its attempts to balance global and democratic inclusion, scholarly openness, and scientific rigor. The author regards several of the more radical decolonial approaches, including the inclusion of a diversity of “indigenous epistemologies,” as incompatible with—and detrimental to—the IAHR’s scholarly standards and raison d’être, and praises Borup for contributing in a nuanced and measured manner to a long-standing and ongoing debate, highlighted in connection with several IAHR world congresses, including the most recent in Kraków in 2025, as well as a summit in Delphi in 2019 and a conference in Tokyo in 2023. DANSK RESUME: Essayet præsenterer og diskuterer først Jørn Borups Decolonising the Study of Religion. Who Owns Buddhism? (2023), herunder Borups karakteristik af afkolonisering som et socialt, ideologisk, men også akademisk og videnskabeligt, indignations- og identitetsbåret aktivistisk projekt. Et projekt, der ser aka-demisk religionsvidenskab, som fx promoveret af IAHR (International Association for the History of Religions (IAHR), som rodfæstet i og fortsat gennemsyret af koloniale, sekulære, euro-og kristocentriske tankegange. Et projekt, der ikke vil blive ved kritikken, men radikalt omkalfatre akademiske og religionsvidenskabelige normer. Med udgangspunkt i Borup spørgsmål om, hvorvidt IAHR fremover vil eller kan undgå at blive påvirket og forandret af mere radikale afkoloniseringstankegange, indsættes Bo-rups fremstilling og kritiske evaluering af afkoloniseringsprojektet i en forskningshistorisk og religionsvidenskabelig kontekst knyttet til IAHR’s globale ekspansion og forsøg på at balancere global og demokratisk inklusion, videnskabelig åbenhed og videnskabelig stringens. Forfatteren ser flere af de radikale afkoloniseringstankegange, herunder inklusion af en mangfold af ‘indigenous epistemologies’, som uforenelige med og gift for IAHR’s videnskabelige standarder og raison d’étre og roser Borup for på nuanceret og sober vis at bidrage til en lang og vedvarende diskussion, accentueret i forbindelse med flere IAHR-verdenskongresser, også den seneste i Kraków 2025 samt et topmøde i Delphi i 2019 og en konference i Tokyo 2023.